Integrated investigation on the synthesis, computational analysis, thermal stability, and performance of eco-friendly chelating agents for calcium ions - Emily S Majanun; Fatin Nur Ain Abdul Rashid; Muhamad Kamil Yaakob; Ahmad Sazali Hamzah; Zurina Shaameri; Karimah Kassim; Noor Hidayah Pungot; Muhamad Azwan Hamali; Ahmad Shalabi Md Sauri; Farhana Jaafar Azuddin; Yon Azwa Sazali; M Zuhaili Kashim; et al. (Penerbit Universiti Kebangsaan Malaysia, 2025)
Several chelating agents, including amine diacetic acid and amino acid diacetic acid, have been synthesized for the purpose of treating and controlling unwanted metal cations applications, specifically targeting divalent ions such as calcium (Ca2+) that contribute to scale formation in high temperature carbonate environments. To evaluate their effectiveness, Density Functional Theory (DFT) calculation was performed to assess electronic reactivity through quantum descriptors including EHOMO, ELUMO, energy gap (ΔE), electron affinity (A), ionization potential (I), electronegativity (χ), global hardness (η), and global softness (σ). A diacetic acid (ADA) exhibited the lowest HOMO-LUMO energy gap, indicating high molecular reactivity toward metal surfaces. Monte Carlo simulations were conducted to determine the most stable adsorption configurations and quantify the adsorption energies of each chelating agent with Ca2+ ions. The ranking of adsorption affinity was found to be: GlnDA > ADA > PDA > BnDA > EDA > BDA, with GlnDA exhibited the highest adsorption energy, suggesting strong adsorption towards Ca ions. In reality, performance study conducted demonstrates that GlnDA exhibits a notable ability to dissolve Ca from carbonate rock under acidic conditions.